Kontribusi Kegiatan Ekstrakulikuler Terhadap Keterampilan Menari Siswa SMA 1-5 Kartika Padang - Azifah Ireta; Fuji Astuti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the extracurricular contribution to the dancing skills of SMA 1-5 Kartika students. This type of research is quantitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data was collected through observation, interviews, and documentation. The steps of analyzing data are collecting data, identifying data, classifying data and inferring data. The results showed that the development of student interest through extracurricular dance is carried out through the planning, implementation and evaluation stages. Planning is carried out through cooperation between school principals, student representatives and coaching teachers so that the implementation of extracurricular activities as self-development can be carried out conducively. The implementation of extracurricular dance activities is carried out outside school hours. Evaluations are carried out by the principal, student representatives, coaches / trainers who are carried out every event, baralek gadang and school farewell. In its implementation, extracurricular dance has been running well and smoothly. Extracurricular dance can develop students' interest in dance in interlectual, spicomotor and spicological aspects. Supporting factors in the implementation of extracurricular dance are the availability of facilities and infrastructure as support in this activity, the quality of trainers / coaches who have knowledge in the field of dance and are able to design this activity, high student interest so that students are the absence of basic student dance so that students are slow to understand the movements given.